Enhanced Electrocatalytic Activity of Pd–Ir–Ni, Pd–Ir–Mo and Pd– Ir–Rh Nanoparticles Supported on Cellulose-based Carbon (CC) for Membraneless Sodium Perborate Fuel Cells (MLSPBFCs) - K. Vijayaramalingam, A. Karthikeyan, V. Selvarani, S. Kiruthika, B. Muthukumaran (Journal of Applied Pharmaceutical Science, 2018)
In the present study, a new concept of fabrication, characterization, and performance of Pd–Ir–M ternary nanoparticles supported on cellulose-based carbon (CC) was proposed with a notion to enhance the electrocatalytic oxidation of hydrogen peroxide. The combination of monometallic Pd/CC, bimetallic Pd–Ir/CC, and tri-metallic Pd–Ir–M/CC (M = Ni, Mo, and Rh) nanoparticles were synthesized by the chemical reduction method assisted by ultrasonication. X-Ray diffraction (XRD), energy dispersive X-Ray spectroscopy (EDX), transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were used for the catalyst characterization. The catalytic activities of electrocatalysts were measured in half-cell experiments using chronoamperometry (CA), CO stripping voltammetry, and cyclic voltammetry (CV). Based on half-cell experiments, electrochemical results showed that tri-metallic Pd– Ir–M nanoparticles display better catalytic activity at room temperature towards hydrogen peroxide oxidation as compared to bimetallic and monometallic catalysts. Based on the experiments carried out on MLSPBFC, Pd–Ir–Ni/ CC displayed a better catalytic activity than all other catalysts synthesized.
Keywords: Sodium perborate, Fuel cell, Hydrogen peroxide, Cellulose based carbon, trimetallic catalyst, Pd– Ir–M.